Surfactant effects in the morphology and the photocatalytic activity of the BaMoO4 crystals - Gouveia, Amanda Fernandes; Bellucci, Gustavo Venancio; Ribeiro, Lara Kelly; Assis, Marcelo; Rosa, Ieda Lúcia Viana; Longo, Elson; Andrés, Juan; San-Miguel, Miguel Angel (Eclética Química, 2022)
This paper discloses the effect of the surfactant sodium dodecyl sulfate (SDS) in the morphology and the photocatalytic activity of BaMoO4 crystals. Experimental techniques were applied to study the order-disorder degree of the samples. First-principles calculations were performed at density functional theory level with the B3LYP hybrid functional. The morphologies were investigated by field emission scanning electron microscopy, and the theoretical crystal shapes were obtained through the Wulff construction. The photocatalytic activity efficiency of the BaMoO4 crystals was tested against the Rhodamine B (RhB) dye. In this paper, BaMoO4 synthesized with SDS by the coprecipitation method presented a monophasic crystal with a disordered structure. In addition, the presence of this surfactant generated pores on the surfaces of the material, and those pores were responsible for the appearance of the adsorptive ability enhancing the adsorption process of the RhB dye in the dark, in absence of ultraviolet light.